2011
DOI: 10.1016/j.bbrc.2011.08.114
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-2 activates NADPH oxidase to increase endoplasmic reticulum stress and human coronary artery smooth muscle cell calcification

Abstract: Bone morphogenetic protein-2 (BMP-2) increases oxidant stress and endoplasmic reticulum (ER) stress to stimulate differentiation of osteoblasts; however, the role of these signaling pathways in the transition of smooth muscle cells to a calcifying osteoblast-like phenotype remains incompletely characterized. We, therefore, treated human coronary artery smooth muscle cells (HCSMC) with BMP-2 (100 ng/ml) and found an increase in NADPH oxidase activity and oxidant stress that occurred via activation of the bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 29 publications
5
76
0
2
Order By: Relevance
“…S4). This is also in agreement with previous findings on the contribution of NOX to BMP2-stimulated osteoblast differentiation [8,37]. However, several open questions such as the nature of connection between ROS production and the activation of PARP1 as well as mediators of downstream signaling remain to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…S4). This is also in agreement with previous findings on the contribution of NOX to BMP2-stimulated osteoblast differentiation [8,37]. However, several open questions such as the nature of connection between ROS production and the activation of PARP1 as well as mediators of downstream signaling remain to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…[25][26][27][28] In endothelial cells (ECs), XBP1 splicing plays diverse roles, including cell proliferation, 26 autophagy response, 29 and apoptosis. 30 In SMCs, bone morphogenetic protein-2 was reported to activate XBP1 splicing, 31 but the exact role of XBP1 in SMCs still remains unclear. In this study, we demonstrated that XBP1 splicing is crucial in PDGF-BB-induced SMC proliferation and contributes to neointima formation after vascular injury.…”
mentioning
confidence: 99%
“…[8][9][10] Recent reports have shown that ER stress occurs during osteogenic differentiation. [17][18][19][20][21] ER stressinduced apoptosis of osteoblasts has also been implicated in the pathogenesis of osteoporosis. [22][23][24][25][26] Our study found that the MC3T3-E1 cells, the mouse calvaria osteoblasts, were led into the decrease of cellular viability in response to ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that several osteogenic cytokines, such as bone morphogenetic protein-2 (BMP-2) could induce osteoblasts ER stress during osteogenic differentiation. 17,18 Some ER stress-associated proteins have a significant role in bone formation. For example, old astrocyte specifically induced substance (OASIS), an ER stress transducer, has been implicated to be involved in bone formation through the transcription of COL1A1 and the secretion of bone matrix proteins.…”
mentioning
confidence: 99%